ANALISIS PERSEPSI FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT USAHA RAKYAT (KUR) BAGI UMKM DI KOTA BATAM (Studi kasus pada Bank BRI) - Raymond Raymond; Nuzul Ikhwal (JURNAL AKUNTANSI BARELANG, 2019)
Lending by banks to SMEs in each region is determined by a number of benchmarks, where one of these standards is the evaluation of the feasibility of SMEs will be given credit, creditworthiness can generally be carried out with due respect to 5 C, which includes: character, capacity, capital, collateral and condition of economy. By using analysis Cochran Q test, the study identifies the Bank that extends credit (KUR) in the city of Batam related implementation aspects 5C lending on SMEs in the city of Batam and to identify variables 5C which are the most dominant as a determinant in lending of SMEs in the city Batam. The results of this study found that the presence of Implementation for all variables 5C on the distribution of small loans in Batam city, where there are 10 variables are the most dominant in the distribution People's Business Credit (KUR) in Batam.